EDUCATIONAL AND ETHICAL VIEWS OF ABDURAHMAN JAMI. PEDAGOGICAL VIEWS OF ALISHER NAVOI. - Kholmamatova , Sevinch; Fayzullayeva , Gulsanam (Journal of Pedagogical and Philological Research, 2026)
This article extensively studies and analyzes the pedagogical, educational, and ethical views of Abdurahman Jami and Alisher Navoi. The article provides a detailed overview of Jami’s thoughts on science and ethics, Sufi education, and teacher-student relationships, as well as Navoi’s ideas on the upbringing of the younger generation, moral virtues, the honor of the teacher, pedagogical responsibility, and the expression of pedagogical concepts in his literary works. A comparative analysis of both thinkers’ perspectives is conducted, highlighting their significance and practical application within the modern pedagogical system. The article is based on scholarly-analytical, historical, cultural, and pedagogical approaches, making it valuable for the fields of pedagogy, literary studies, and spirituality.